2016
DOI: 10.1093/pasj/psw081
|View full text |Cite
|
Sign up to set email alerts
|

Large X-ray flares on stars detected with MAXI/GSC: A universal correlation between the duration of a flare and its X-ray luminosity

Abstract: 23 giant flares from 13 active stars (eight RS CVn systems, one Algol system, three dMe stars and one YSO) were detected during the first two years of our all-sky X-ray monitoring with the gas propotional counters (GSC) of the Monitor of All-sky X-ray Image (MAXI). The observed parameters of all of these MAXI/GSC flares are found to be at the upper ends for stellar flares with the luminosity of 10 31−34 ergs s −1 in the 2-20 keV band, the emission measure of 10 54−57 cm −3 , the e-folding time of 1 hour to 1.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 117 publications
1
48
0
Order By: Relevance
“…In the model described above, and based on the properties such as fluence and duration, all superflares would have been within reach of CTA. In a systematic search for flares with the MAXI/GSC instrument aboard the ISS, Tsuboi et al (2016) found only 13 stars to be flaring out of a population of 256 active binary stars (Eker et al 2008). Some of these stars flared multiple times and experienced radiative energy releases of up to 10 39 ergs.…”
Section: Expectation For the Population Of Nearby Young Starsmentioning
confidence: 99%
“…In the model described above, and based on the properties such as fluence and duration, all superflares would have been within reach of CTA. In a systematic search for flares with the MAXI/GSC instrument aboard the ISS, Tsuboi et al (2016) found only 13 stars to be flaring out of a population of 256 active binary stars (Eker et al 2008). Some of these stars flared multiple times and experienced radiative energy releases of up to 10 39 ergs.…”
Section: Expectation For the Population Of Nearby Young Starsmentioning
confidence: 99%
“…MAXI detected more than one-hundred flares on twenty-eight low-mass stars; fourteen RS CVn systems, one Algol system (Algol), ten dMe stars, one dKe star, one Young Stellar Object (TWA-7) and one K-type variable star. The detection of the flare from TWA-7 and the results from the first two-year monitoring with MAXI have been already reported in Uzawa et al (2011) [2] and Tsuboi et al (2016) [3], respectively. Most of the categories are classified as active binaries, which consist of the pair of a sub-giant and a main sequence, a pair of a giants and main-sequence, and a pair of two main-sequence stars.…”
Section: Introductionmentioning
confidence: 54%
“…A Unified Correlation between the Duration and the X-ray Luminosity in Stellar Flares Y. Tsuboi type star) [15]. The physical parameters of the flares are very large for stellar flares in all of the followings: the X-ray luminosity L X (10 31−34 ergs s −1 in the 2-20 keV band), the emission measure EM (10 54−57 cm −3 ), the e-folding time (10 3−6 s), and the total energy released during the flare (10 34−39 ergs).…”
Section: Pos(multif2017)060mentioning
confidence: 99%
“…The number of the detection of the large flare was increased significantly. Tsuboi et al (2016) found the correlation between X-ray bolometric luminosity and the duration time which holds from solar microflares to giant stellar flares detected with MAXI [15].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation